The experimental study on indoor and outdoor penetration coefficient of atmospheric fine particles. (15th March 2018) - Lv, Yang; Wang, Haifeng; Wei, Shanshan; Wu, Tingfeng; Liu, Tong; Chen, Bin
Abstract: In recent years, haze pollution of China has become increasingly serious. Outdoor particles can enter the room through the building crack. Therefore, it is of great significance to study the indoor and outdoor penetrating and transport characteristics of fine particles. In this paper, the main factors affecting the penetration coefficient are quantitatively analyzed by combining theoretical and experimental research. The results indicate that there is no obvious function between the pressure difference and the penetration coefficient when the crack height 1 mm, but they can be unified with a linear function when the crack height 0.25 mm. The effect of the crack height and length on penetration coefficient is related to the maximum net displacement of particles. The smaller the crack height (H), the longer the crack length (L) and the smaller the pressure difference (ΔP) would cause the greater the decrease of the penetration coefficient as the particle size increases. Temperature and relative humidity have no significant correlation with the penetration coefficient. The semi-empirical formula of penetration coefficient is established based on the correlation analysis and the theory of penetrating coefficient, which has the advantages of high accuracy, simple form and easy to measurement. Highlights: The penetration coefficient is used to describe the particles penetrating characteristics through the enclosure structure. The main factors affecting penetration coefficient are quantitatively analysed by theoretical and experimental research. The semi-empirical formula of penetration coefficient is established based on the theoretical and experimental results.